Dielectrophoresis Effect of Dielectric Liquids with Suspended Cellulose Impurities under DC Electric Field - Muhamad Hafiy Syazwan Zainoddin; Hidayat Zainuddin; Aminudin Aman (International Journal of Electrical and Computer Engineering (IJECE), 2017)
For decades, petroleum-based mineral oils are the insulating media conventionally used in the industry, particularly for high voltage (HV) applications. However, due to the disadvantages of mineral oils, there is growing interest in replacing these oils with environmentally friendly alternatives in order to fulfill the demanding requirements of dielectric liquids.  One of the promising substitutes for mineral oils is ester oils. Nevertheless, the implementation of ester oils is not widespread compared with mineral oils due to the lack of understanding on the performance of ester oils in HV applications. Hence, the objective of this study is to investigate the bridging phenomenon of two dielectric liquids with different viscosities: palm fatty acid ester and mineral oil under the influence of direct current electric field. The results show that oil viscosity plays an important role in the formation of cellulose bridge and breakdown behavior.